2007
DOI: 10.1086/522429
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity and Active Human Cytomegalovirus Infection in Patients with Septic Shock

Abstract: A proinflammatory immune response may contribute to CMV reactivation in patients with septic shock. Adaptive T cell immunity, more likely than NK cell immunity, may contribute to termination of active CMV infection without antiviral therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
52
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 28 publications
9
52
0
1
Order By: Relevance
“…Between these extremes there are other less well-understood possibilities where immune surveillance may be unable to prevent viral reactivation, but it still may be competent in inhibiting systemic uncontrolled infection. Indeed, recent reports showed that critically ill immunocompetent patients and patients with septic shock may undergo systemic, but self-limiting, reactivation of HCMV (5,6). Furthermore, immunosuppressed patients transplanted with solid organs are susceptible to a statistical increase in mortality, transplant rejection, accelerated vascular diseases, and injury from other pathogens (7) that can be prevented by specific anti-HCMV therapy (8,9).…”
mentioning
confidence: 99%
“…Between these extremes there are other less well-understood possibilities where immune surveillance may be unable to prevent viral reactivation, but it still may be competent in inhibiting systemic uncontrolled infection. Indeed, recent reports showed that critically ill immunocompetent patients and patients with septic shock may undergo systemic, but self-limiting, reactivation of HCMV (5,6). Furthermore, immunosuppressed patients transplanted with solid organs are susceptible to a statistical increase in mortality, transplant rejection, accelerated vascular diseases, and injury from other pathogens (7) that can be prevented by specific anti-HCMV therapy (8,9).…”
mentioning
confidence: 99%
“…During the follow-up the frequency of Th1-cells signiWcantly increased in patients with septic shock following reactivation and recurrence [13]. The increase in CD4+ HCMV speciWc Th1-cells was presumably accompanied by increased activity of HCMV speciWc CD8+ cytotoxic Tcells as was shown before for patients after transplantation [39].…”
Section: => Direct Effects Of Disease (End-organ-disease)mentioning
confidence: 63%
“…We could show that HCMV recurrence was detected very similarly in groups with and without HCMV reactive Th1-cells, which means that CMV reactivation at the cellular level is not caused by immunosuppression. HCMV recurrence was followed by an increase of HCMV reactive Th1-cells which mostly failed to appear in the group without pp65-antigenemia [13] However, a subgroup of pp65-negative seropositive patients displayed a strong increase in HCMV reactive Th1-cells (Fig. 1) and we propose that reactivation without HCMV recurrence could have been the basis for stimulation and subsequent proliferation of HCMV reactive Th1-cells.…”
Section: Reactivationmentioning
confidence: 75%
See 2 more Smart Citations